2021
DOI: 10.1038/s41380-021-01068-3
|View full text |Cite
|
Sign up to set email alerts
|

Brain cells derived from Alzheimer’s disease patients have multiple specific innate abnormalities in energy metabolism

Abstract: Altered energy metabolism has been implicated both in aging and the pathogenesis of late-onset Alzheimer’s disease (LOAD). However, it is unclear which anomalies are acquired phenotypes and which are inherent and predispose to disease. We report that neural progenitor cells and astrocytes differentiated from LOAD patient-derived induced pluripotent stem cells exhibit multiple inter-related bioenergetic alterations including: changes in energy production by mitochondrial respiration versus glycolysis, as a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 51 publications
(68 reference statements)
9
71
0
Order By: Relevance
“…Since glutamine is derived from the TCA cycle intermediate α-ketoglutarate via glutamate, astrocyte TCA cycle function is crucial for glutamine synthesis (Swanson and Graham, 1994). Multiple studies have revealed impaired astrocytic energy metabolism in AD (Oksanen et al, 2017;Dematteis et al, 2020;Andersen et al, 2021a;Ryu et al, 2021). It could, therefore, be speculated that the reduced synthesis of glutamate from oxidative leucine metabolism observed in the AD astrocytes may be caused by deficient astrocyte TCA cycle function, which may further hamper glutamine synthesis in AD.…”
Section: Bcaa Metabolism In Admentioning
confidence: 99%
“…Since glutamine is derived from the TCA cycle intermediate α-ketoglutarate via glutamate, astrocyte TCA cycle function is crucial for glutamine synthesis (Swanson and Graham, 1994). Multiple studies have revealed impaired astrocytic energy metabolism in AD (Oksanen et al, 2017;Dematteis et al, 2020;Andersen et al, 2021a;Ryu et al, 2021). It could, therefore, be speculated that the reduced synthesis of glutamate from oxidative leucine metabolism observed in the AD astrocytes may be caused by deficient astrocyte TCA cycle function, which may further hamper glutamine synthesis in AD.…”
Section: Bcaa Metabolism In Admentioning
confidence: 99%
“…A low pHi and pHe rapidly decreases neuronal transmission and activity, preceding the onset of neural cell death by apoptosis [17][18][19][20][21], the same as ASIC1 does [22]. In the same vein, accumulation of β-amyloid (βA) is directly induced by acidosis [11][12][13][14][16][17][18][19][20][21][22]104,106,107] (Figure 2 and Box 1). Further, low neural cell pHs induce protein aggregation, mitochondrial dysfunction, oxidative stress and neuroinflammation, which are hallmarks of Parkinson's disease (PD) [23].…”
Section: Cellular and Microenvironmental Acid-base Abnormalities In Neurodegenerative Diseases (Box 1)mentioning
confidence: 91%
“…Intracellular acidification is more pronounced in the brain of AD patients [11,107], while ßA aggregation in a mice model of AD is induced by acidosis and reverted upon microenvironmental alkalization, just as happens when using plasma rich in growth factors (PRGF) [16,21,[24][25][26]. Lowering pHi of neurons from 7.36 to 7.09/7.00 through exposure to nitric oxide (NO) sets in motion a programmed cell death program, increasing DNA fragmentation and decreasing cell survival ("low pHi-mediated metabolic collapse") [7,8,11,[27][28][29].…”
Section: Cellular and Microenvironmental Acid-base Abnormalities In Neurodegenerative Diseases (Box 1)mentioning
confidence: 99%
“…Ryu and collaborators compared neural progenitor cells and astrocytes differentiated from late-onset AD patients. The authors found a significant downregulation of lactate dehydrogenase A in both cell types and that astrocytes from late-onset AD have a reduced metabolism of lactate [97].…”
Section: The Role Of L-lactate In Diseasementioning
confidence: 94%